Teaching Short - Circuit Calculation with Off - Nominal Turns Ratio Transformers - Allen A. Castillo (UIKTEN, 2021)
Teaching short-circuit analysis is conducted primarily through case studies; however, there are not many validated short-circuit studies available on the subject, especially when considering off-nominal turns ratio transformers. In order to improve the teaching of short-circuit analysis, a three phase short-circuit study in an industrial system according to ANSI/IEEE standards by means of Zmatrix method is presented; two case studies are considered: the industrial system with nominal and offnominal turns ratio transformers, in both cases the step by step solution is given in an explicit manner and the analytical results are validated through software simulation.